Perceived challenges to public health in Central and Eastern Europe: a qualitative analysis - Müller-Nordhorn, Jacqueline (BioMed Central, 2012)
BACKGROUND: There is a major gradient in burden of disease between Central and Eastern Europe compared to Western Europe. Many of the underlying causes and risk factors are amenable to public health interventions. The purpose of the study was to explore perceptions of public health experts from Central and Eastern European countries on public health challenges in their countries. METHODS: We invited 179 public health experts from Central and Eastern European countries to a 2-day workshop in Berlin, Germany. A total of 25 public health experts from 14 countries participated in May 2008. The workshop was structured into 8 sessions of 1.5 hours each, with the topic areas covering coronary heart disease, stroke, prevention, obesity, alcohol, tobacco, tuberculosis, and HIV/AIDS. The workshop was recorded and the proceedings transcribed verbatim. The transcripts were entered into atlas.ti for content analysis and coded according to the session headings. After analysis of the content of each session discussion, a re-coding of the discussions took place based on the themes that emerged from the analysis. RESULTS: Themes discussed recurred across disease entities and sessions. Major themes were the relationship between clinical medicine and public health, the need for public health funding, and the problems of proving the effectiveness of disease prevention. Areas for action identified included the need to engage with the public, to create a better scientific basis for public health interventions, to identify “best practices” of disease prevention, and to implement registries/surveillance instruments. The need for improved data collection was seen throughout all areas discussed, as was the need to harmonize data across countries. CONCLUSIONS: To reduce the burden of disease across Europe, closer collaboration of countries across Europe seems important in order to learn from each other. A more credible scientific basis for effective public health interventions is urgently needed. The monitoring of health trends is crucial to evaluate the impact of public health programmes.